An ecological investigation of average and peak external load intensities of basketball skills and game-based training drills - Sansone, Pierpaolo; Gasperi, Lorenzo; Makivic, Bojan; Gomez-Ruano, Miguel; Tessitore, Antonio; Conte, Daniele (Biology of Sport, 2023)
This study quantified average and peak external intensities of various basketball training drills. Thirteen youth male basketball players (age: 15.2±0.3 years) were monitored (BioHarness-3 devices) to obtain average and peak external load per minute (EL·min−1; peak EL·min−1) during team-based training sessions. Researchers coded the training sessions by analysing the drill type (skills, 1vs1, 2vs2, 3vs0, 3vs3, 4vs0, 4vs4, 5vs5, 5vs5-scrimmage), court area per player, player’s involvement in the drill (in percentage), playing positions (backcourt; frontcourt) and competition rotation status (starter; rotation; bench). Separate linear mixed models were run to assess the influence of training and individual constraints on average and peak EL·min−1. Drill type influenced average and peak EL·min−1 (p 0.05), except for a moderately higher EL·min−1 in starters compared to bench players. The external load intensities of basketball training drills substantially vary depending on the load indicator chosen, the training content, and task and individual constraints. Practitioners should not interchangeably use average and peak external intensity indicators to design training but considering them as separate constructs could help to gain a better understanding of basketball training and competition demands.